A correlation study on the oral hygiene status and the academic profile of the U.P.C.D. students - Galvez, Gina
This study was designed to provide information on the effect and relationship of some personal and academic variables to the oral hygiene status of the students on the basis of GWA and grads in Periodontology, both clinical and theoretical and the personal variables like age, sex, manner of toothbrushing, scaling and polishing. Only 178 out of 200 students were examined for oral hygiene using OHI-S by Greene and Vermilleon. Results showed inverse relationship between GWA and OHS scores, the grades of all the rest of the students regardless of sex and year level appear to have no bearing on the oral hygiene status of the students. Knowledge of preventive periodontology does not improve the oral hygiene status of seniors over others. And personal variables like age, sex, year level, frequency and manner of brushing and last scaling and polishing do not affect the state of oral hygiene of the subjects included in the study.